HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN DEDUKTIF DAN INDUKTIF - Intan Nadiroh; Cahya Mauidho Hasanah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2021)
Abstract: The application of a deductive approach is an approach that uses logic to draw one or more conclusions based on a given set of premises. In this case, the researcher chose material regarding the properties of the spatial structure applied in class V-A Madrasah Ibtidaiyah Bahrul Ulum Tambakberas. The application of the inductive approach is an approach that emphasizes observations first, then draws conclusions based on these observations. In this case, the researcher chose material regarding the properties of spatial structures that were applied in class V-B Madrasah Ibtidaiyah Bahrul Ulum Tambakberas Jombang. The results of the simple linear regression equation show that the use of comparison of inductive learning outcomes indicates a better goal, so it can improve the learning outcomes of fifth grade students at MI Bahrul Ulum Tambakberas Jombang. While the results of partial hypothesis testing on the regression coefficients of each predictor obtained the value of T table = ta / 2 ; df (n-2) = t 5%/2; df (56-2) = t 0.025; df(54) = 2.00. The hypotheses of each predictor are as follows: The results of the partial test output (t) obtained the value of T arithmetic = 9.00 indicating that T count > T table that is 9.00 > 2.00 and the standard significance / probability value (a) 0.000 < 0.05 then Ho is rejected and Ha is accepted . This shows that the predictor regression coefficient of the inductive approach has an effect on student learning outcomes.